HUBUNGAN PERSONAL HYGIENE DENGAN PEDIKULOSIS CAPITIS PADA SISWI MTs JA-ALHAQ KOTA BENGKULU: The Relationship Between Personal Hygiene and Pediculosis capitis In Students At MTs Ja-Ahaq Bengkulu City - Inayah Hayati; Enda Nabila; Septi Puspitasari (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
This cross-sectional study involved 67 female students in grade VIII at MTS Ja-alhaq as the sample. The objective was to analyze the relationship between personal hygiene and pediculosis capitis infection among female students at MTS Ja-alhaq in Bengkulu City. Pediculus humanus capitis is a parasite that causes infection of the scalp and hair, known as pediculosis capitis. The results showed that 44 respondents (65.7%) had Pediculosis capitis found and 23 (34.3%) were not found, The chi-square test (Pearson chi-square) revealed a significant correlation between personal hygiene and pediculosis capitis, with a ρ value of 0.000 < 0.05. Of the respondents, 16 (23.9%) demonstrated good personal hygiene, while 51 (76.1%) had poor personal hygiene. Thus, there is a statistically meaningful relationship between personal hygiene and pediculosis capitis infection.